2016
DOI: 10.1016/j.neulet.2016.09.057
|View full text |Cite
|
Sign up to set email alerts
|

Combined damage produced by multiple mild cerebral insults assessed using MRI in neonatal rats

Abstract: The extent of damage produced by a minor neonatal stroke followed by a diffuse HI two days later results in heterogeneous enhancement of T, ADC and histological injury near the lesion. Surgical procedures including mechanical head manipulation followed by HI also produced some enhanced heterogeneity of hypoxic-ischemic injury affirming the need for sham controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Such enhancement extended to an adjacent lesion region in an adjacent MR slice when there was an acute but not chronic recovery time between insults. Heterogeneous increases in T 2 within the vicinity of a PT, generally consistent with those of the present study, have also been observed in neonatal rats subjected to a minor PT followed 2 days later by unilateral cerebral hypoxia–ischemia [16]. …”
Section: Discussionsupporting
confidence: 90%
“…Such enhancement extended to an adjacent lesion region in an adjacent MR slice when there was an acute but not chronic recovery time between insults. Heterogeneous increases in T 2 within the vicinity of a PT, generally consistent with those of the present study, have also been observed in neonatal rats subjected to a minor PT followed 2 days later by unilateral cerebral hypoxia–ischemia [16]. …”
Section: Discussionsupporting
confidence: 90%